2014 IEEE International Conference on Big Data (Big Data) 2014
DOI: 10.1109/bigdata.2014.7004422
|View full text |Cite
|
Sign up to set email alerts
|

Spatial big data analytics of influenza epidemic in Vellore, India

Abstract: The study objective is to develop a big spatial data model to predict the epidemiological impact of influenza in Vellore, India. Large repositories of geospatial and health data provide vital statistics on surveillance and epidemiological metrics, and valuable insight into the spatiotemporal determinants of disease and health. The integration of these big data sources and analytics to assess risk factors and geospatial vulnerability can assist to develop effective prevention and control strategies for influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…A field study indicated that an increased risk of influenza in horses was associated with Wv of >30 km/h (Firestone et al, 2012). In India, Wv was positively correlated to an increase risk for influenza (H1N1) (linear regression coefficient: 1.02, p < 0.05) (Lopez et al, 2014). This may due to the effects of high wind speed on the longer travel of air-borne aerosols, which contributed to the transmission of influenza virus (Ssematimba et al, 2012).…”
Section: N=100%mentioning
confidence: 99%
“…A field study indicated that an increased risk of influenza in horses was associated with Wv of >30 km/h (Firestone et al, 2012). In India, Wv was positively correlated to an increase risk for influenza (H1N1) (linear regression coefficient: 1.02, p < 0.05) (Lopez et al, 2014). This may due to the effects of high wind speed on the longer travel of air-borne aerosols, which contributed to the transmission of influenza virus (Ssematimba et al, 2012).…”
Section: N=100%mentioning
confidence: 99%
“…The communicable diseases that were chosen for this experiment were Influenza Virus, RS-Virus, Rhinovirus and Pneumonia [1].…”
Section: Resultsmentioning
confidence: 99%
“…With this form of vibrancy, people are placing an increased importance on health and the threat of diseases [1]. The health officials are doing everything they can to obtain timely information on epidemic outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, health care systems are rapidly adopting clinical data, which will rapidly enlarge the size of the health records that are accessible, electronically [3,4]. A recent study expounds, six use cases of big data to decrease the cost of patients, triage and readmissions [5].…”
Section: Introductionmentioning
confidence: 99%